2018
DOI: 10.1042/cs20180005
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in mitochondrial dynamics by p66Shc lead to renal tubular oxidative injury in human diabetic nephropathy

Abstract: Renal tubular injury is increasingly being recognized as an early characteristic of diabetic nephropathy (DN). Mitochondrial dynamic alterations and redox protein p66Shc-mediated oxidative stress are both critical for ensuing diabetic tubular cell injury and apoptosis; whether these two processes are interlinked remains unclear. In the present study, we observed changes in mitochondrial morphology and expression of associated proteins in tubules of patients with DN. We demonstrated mitochondrial fragmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 49 publications
2
47
0
Order By: Relevance
“…Similar findings have also been reported in another study albeit in proximal tubular biopsies obtained from people with diabetes (pooled T1D and T2D) and diabetic nephropathy (Zhan et al., ). In particular, this study found an increase in superoxide (dihydroethidium staining), cytochrome c release (indirectly indicates increased opening of mPTP), and perturbations in mitochondrial dynamics (decreased expression of protein markers of mitochondrial fusion, increased expression of protein markers of mitochondrial fission, increased and scattered mitochondrial fragments, and remodelled mitochondrial cristae).…”
Section: Type 1 Diabetes: Beyond Skeletal Musclesupporting
confidence: 90%
“…Similar findings have also been reported in another study albeit in proximal tubular biopsies obtained from people with diabetes (pooled T1D and T2D) and diabetic nephropathy (Zhan et al., ). In particular, this study found an increase in superoxide (dihydroethidium staining), cytochrome c release (indirectly indicates increased opening of mPTP), and perturbations in mitochondrial dynamics (decreased expression of protein markers of mitochondrial fusion, increased expression of protein markers of mitochondrial fission, increased and scattered mitochondrial fragments, and remodelled mitochondrial cristae).…”
Section: Type 1 Diabetes: Beyond Skeletal Musclesupporting
confidence: 90%
“…It is well known that increased p66shc expression is closely associated with oxidative stress and recent study reported that oxidative stress is related to cytochrome C-mediated apoptosis. Consistent evidence demonstrated that high expression of p66shc in ischemia reperfusion [26], renal tubular oxidative injury [30], angiotensin II-induced mouse hippocampal HT22 cells apoptosis [31] could active cytochrome Cmediated apoptotic pathways. However, the relationship between p66shc and cytochrome C in NAFLD haven't been clearly demonstrated.…”
Section: Agingmentioning
confidence: 71%
“…Alterations in mitochondria function determine the intracellular accumulation of lipids and further lipotoxic actions, as reported in both glomeruli and tubules [159][160][161]. The proximal tubule has highly specialized metabolic machinery, which needs a fine energy balance.…”
Section: Mitochondria As the Main Target Of Lipotoxicity-kidney Diseasementioning
confidence: 99%
“…Recent studies have highlighted the renoprotective role of cardiolipin, a unique phospholipid present in the mitochondrial inner membrane, necessary for the formation and maintenance of mitochondrial cristae structure [158,159,165]. The prevention of cardiolipin peroxidation improves the efficiency of ATP production through the oxidative phosphorylation (OXPHOS) process, restoring mitochondrial bioenergetics [160,161]. Indeed, when phosphorylation capacity is exceeded, mitochondria are disturbed and, as a consequence, non-oxidized lipids are accumulated.…”
Section: Mitochondria As the Main Target Of Lipotoxicity-kidney Diseasementioning
confidence: 99%